The Zone of Proximal Development Concept: A Psychological Instrument for Improving Pedagogical Practice - Venet, Michèle; Correa Molina, Enrique (Pensando Psicología, 2014)
Competency-based training requires universities to not only look at the theories that underpin different visions of education and teaching, but also at their application in a school context. Moreover, it is hoped that during their education, students will be able to integrate theory and practice; however, this poses a problem for them. To overcome the difficulty in integrating theory and practice, some authors have proposed the use of reflective practice, and we therefore hypothesized that the concept of the zone of proximal development (zpd), created by Soviet psychologist Lev Vygotsky, could be used as a psychological instrument to promote reflection on practice for students undertaking our Bachelor’s Degree in School and Social Adaptation at Université de Sherbrooke, Canada. To test our hypothesis, we worked on the practice of 20 students from this course according to the concept of zpd. The results show that the concept is an effective psychological instrument for promoting the integration of theory and practice.
Keywords: learning; university student; professional training; teacher trainer; zone of proximal development